Assessing treatment adherence in hypertensive patients: a cross sectional study - Gore, Alka Dilip; Kadam, Yugantara Ramesh (International Journal Of Community Medicine And Public Health, 2017)
Background: The complications of hypertension are all related to the poor adherence to treatment. To prevent high blood pressure, one has to make modifications in lifestyle and diet along with medications. So the study is planned to assess the treatment adherence in hypertensive patients. Methods: a hospital based cross-sectional study was conducted within 6 months to determine the level of adherence and to find out the risk factors associated with non-adherence to pharmacological & non-pharmacological treatment among the hypertensive patients attending a tertiary care hospital. Using a pre-tested proforma, information about adherence to antihypertensive therapy was collected from known 220 hypertensive patients, attending Medicine OPD and willing to participate in the study. Collected data was analysed using SPSS-22. Chi-square test and Binary logistic regression were used for analysing the data. Results: Adherence to pharmacological treatment is 62.7%, while adherence to non-pharmacological therapy like reduction of salt (79.5%), reduction of oil (80.9%), increase in green leafy vegetables (59.3%), and regular exercise is (47.7%). When binary logistic regression was applied for different drug therapies, education and residence were found as best and significant predictors. Conclusions: Non-adherence was seen in illiterates and rural resident hypertensive patients. Cost of medication is one of the important issues for non-adherence.